Promotions and status motives’ influence on green products' desirability - Martins, Ana Sofia Nunes Teles von Hafe (2020)
What are the factors influencing consumers’ green behaviours? Past studies have been discussing this topic, assigning responsibility to different aspects namely economic incentives (Rational Economic Perspective) and genuine concern for the environment (Environmental Concern Perspective). Yet, as social creatures, individuals’ behaviours are also strongly influenced by social factors such as one’s motivation to have high social status and a positive reputation. Drawing on the Costly Signalling Theory, status driven consumers are more predisposed to forgo luxurious products, paying instead more for green options in order to signal their altruism. Assuming that, this research aims to confirm that eliciting status motives incentivizes consumers to prefer green products which are more expensive. Additionally, it is hypothesised that status seekers’ desirability for green products does not decrease when these are temporarily in promotion, since others do not know the context in which the product was bought. Hence, these consumers’ social identity and reputation ends up not being damaged as they continue to be able to signal their self-sacrifice before relevant others. The present research shows that status motives can lead to higher preferences for expensive green products, since buying them grants individuals with reputational benefits. Consequently, status seekers can be considered as less price sensitive than those who are not motivated to attain status. However, contrary to what the signalling literature would predict, when presented with the possibility of buying green products for a promotional price, status driven consumers do not lose their rational thinking, showing a higher preference for the available opportunity.